Involute Teeth with Variable Base Diameter. Issue 4 (November 2020) - Seregin, A; Kravtsov, A
Abstract: The article presents the results of theoretical and experimental research. The reserve of increasing the durability of gears of machines and mechanisms and reducing the costs of their maintenance and repair is shown to reduce wear of the surfaces of the teeth. The dependences for the calculation and construction of the profile of the teeth of the wheels, providing a decrease in the coefficient of relative slip. Using formulas in polar coordinates for the angle of deployment of the tooth profile involute, a new shape of the lateral profile of the gear teeth is obtained.